Are Passive Institutional Investors Engaged Monitors or Risk-Averse Owners? : Both! - Yang, Yuanchen (IMF Working Papers; Working Paper ;, 2021)
We differentiate the effects of passive institutional investors, which mainly refer to index funds that adopt a passive portfolio strategy, on firms' innovation activities and innovation strategies. Relying on plausibly exogenous variation in passive institutional ownership generated by Russell 1000/2000 index reconstitutions, we find that, with larger passive institutional ownership, while firms' countable innovation activities increase, they shift their innovation strategies by focusing more on exploitation of existing knowledge instead of exploring new technology. Enhanced monitoring by passive institutional investors through active votes could explain their positive effects on firms' innovation activities. Increasing risk aversion on the part of passive institutional investors appears the underlying force that drives firms' shift to incremental innovation. Our paper uncovers a subtle relation between institutional investors and innovation, which is largely ignored by earlier studies.